Enhancing Competency and Skills Through Industrial Training Programs and Knowledge Management: A Comprehensive Analysis - Morteza Piri; Majid Abdi (goodwood publishing, 2026)
Purpose: This study examines the impact of industrial training programs on enhancing workforce competency and bridging the gap between theoretical knowledge and practical application. By analyzing employer and employee perspectives, the study highlights the role of structured training initiatives in fostering industry-relevant skills, professional development, and effective knowledge transfer. Methods: A comprehensive statistical analysis using predictive modeling techniques was employed to assess training effectiveness. Data were collected from employees, students, and supervisors to evaluate skill acquisition, industry preparedness, workplace adaptability, and training outcomes. Results: The findings indicate that industrial training significantly improves communication skills, problem-solving abilities, research orientation, and self-confidence. Employers report enhanced workforce readiness, while trainees acknowledge greater adaptability, continuous learning orientation, and improved understanding of real-world work environments. Conclusions: The study underscores the transformative impact of industrial training on workforce competency, emphasizing its role in aligning academic curricula with industry demands. Structured mentorship, effective feedback systems, and strengthened industry–academia collaboration are essential for optimizing training effectiveness. Limitations: The study is limited to a specific geographic context (Iran) and sector (polytechnic institutions), which may restrict generalizability. In addition, reliance on self-reported data may introduce response bias. Future studies should apply longitudinal designs and examine diverse industrial settings. Contributions: This study contributes to the literature on workforce development and knowledge management by providing empirical evidence on how industrial training bridges theory–practice gaps, strengthens competency development, and supports sustainable industry–academia partnerships.